Normalized CES supply-side system approach: How to replicate Klump, McAdam, and Willman (Review of Economics and Statistics, 2007) - Gerald Eric Daniels; Venoo Kakar (Kiel Institute for the World Economy (IfW), 2017)
This paper lays out a replication plan for the influential paper by Klump et al. (Factor Substitution and Factor-augmenting Technical Progress in the United States: a Normalized Supply-side System Approach, Review of Economics and Statistics, 2007) on using a normalized CES supply-side system approach to estimate the value of the elasticity of substitution between factors of production and identify the growth patterns for biased technical progress. The authors begin with a general discussion of basic principles on carrying out a replication study. Further, they outline key steps to follow to replicate the chosen paper and establish criteria that can be used to determine if the replication confirms or disconfirms the original findings. This paper contributes to the increased interest in improving replications in economics research.
Keywords: O41; O47; E24; 330; Elasticity of substitution; human capital; economic growth; factor shares; CES production function